The efficiency and safety of Shengxuening tablet on treating and preventing iron deficiency anemia: A systematic review and meta-analysis - Zhang, Yanyu; Lv, Yan; Sun, Yan; Li, Yumeng; Wang, Dehao; Niu, Jicong; Zhao, Pei; Zhang, Mei; Wang, Mingjing; Liu, Weiyi; Hu, Xiaomei (Frontiers in Pharmacology, 2022)
Background: Iron deficiency anemia (IDA) is a public health problem worldwide. Shengxuening Tablet (SXN) has been used to treat various types of anemia with high efficiency. Objective: To evaluate the preventive and therapeutic efficiency and safety of SXN on IDA. Methods: We searched Pubmed, Embase, Web of Science, Cochrane, China Knowledge Network, China Biomedical Literature Database, Wanfang Data Knowledge Service Platform and China Science and Technology Journal Database for clinical trials up to June 2022 and performed a systematic review and meta-analysis. Results: 39 trials involving 4562 cases were included. Meta-analysis in children showed that compared to iron supplementations, the ability of SXN in improving hemoglobin (Hb), mean corpuscular volume (MCV), mean corpuscular hemoglobin (MCH), mean corpuscular hemoglobin concentration (MCHC), total serum iron (SI), serum ferritin (SF) levels and downregulating total iron binding capacity (TIBC) was comparable, and SXN significantly raised IDA effective rates [RR = 1.06, 95% CI (1.01, 1.12), p = 0.03], with less adverse events [RR = 0.20, 95% CI (0.13, 0.31), p＜0.00001]. Meta-analysis in adults showed superior effect of SXN in improving RBC [MD = 1.30, 95% CI (0.89, 1.70), p＜0.00001], Hb [MD = 20.46, 95% CI (14.61, 26.31), p＜0.00001], MCV [MD = 6.71, 95% CI (4.4, 9.02), p＜0.00001], SI [MD = 7.21, 95% CI (5.39, 9.03), p＜0.00001] and TSAT [MD = 8.13, 95% CI (6.67, 9.59), p＜0.00001]. SXN also contributed to reduced adverse events [RR = 0.26, 95% CI (0.19, 0.36), p＜0.00001], less adverse pregnancy outcomes [RR = 0.34, 95% CI (0.2, 0.57), p＜0.00001] and lower anemia recurrence rates during pregnancy [RR = 0.29, 95% CI (0.1, 0.84), p = 0.02]. For preventive purpose, SXN significantly improved RBC count [MD = 0.45, 95% CI (0.01, 0.89, p = 0.04], and reduced the risk of IDA incidence during pregnancy [RR =0.4, 95% CI (0.17, 0.95, p = 0.04]. Conclusions: SXN exerted promising efficiency in the treatment and prevention of IDA, and it outperformed routine iron formulations in terms of safety, which renders SXN as a reliable treatment regimen for IDA.